Wear behavior of silica-infiltrated monolithic zirconia: Effects on the mechanical properties and surface characterization - Alves, Larissa Marcia Martins [UNESP] (2022)
The objective of this study was to assess the wear behavior and its effects on the flexural strength of silica-infiltrated zirconia compared to glaze and polishing finishing treatments. To do so, disc-shaped samples of a second-generation zirconia were prepared and divided into three groups: silica infiltration, glazing, or polishing. Half of the samples of each finishing were subjected to sliding wear testing using a steatite antagonist. The discs and antagonists had their volume loss measured. The wear-tested and the other half of samples were subjected to biaxial flexural strength testing and the following characterization analyses were also performed: roughness, hardness, X-ray diffraction, profilometry, and scanning electron microscopy (SEM). Data were evaluated with ANOVA and Weibull analyses. Glazing caused greater antagonist volume loss, followed by silica infiltration, and polishing. Silica-infiltrated zirconia surface was similarly worn to polished, which was lower than that for glazed zirconia. Polished zirconia presented the highest flexural strength. However,the strength decreased and became similar in all worn groups. Silica infiltration showed slightly lower characteristic strength after sliding wear. The highest roughness and hardness values were observed on glazed zirconia. These values decreased after wear testing and became similar to the other groups. SEM evidenced an irregular surface for glazing. No phase transformation occurred after sliding wear. Despite producing some volume loss on zirconia and antagonist surfaces, silica infiltration is a promising alternative for finishing monolithic restorations. Moreover, the damage caused by sliding wear leads to decreasing the strength of zirconia regardless of the surface finishing.